Perception of health personnel regarding the treatment received in times of pandemic in Cali in 2020. - Bedoya-Jojoa, Christian Mauricio (2022)
Perception is a process in which the stimuli that were received by the different senses are organized and interpreted and that help to identify objects and events to later give meaningto said element or process, which extrapolating it to this context refers to the how the human talent in health perceives that theyare treating during their work activities and more so in the midst of a pandemic that in itself is already something epidemiologically drasticfor a society. Therefore, this research had the objective of knowing the perception of health personnel regarding the treatment received in times of pandemic in the city of Cali-Colombia in the year 2020; For this, a survey-type instrument was applied to various health professionals, for subsequent statistical analysis in the "R" program. As a global result, itwas obtained that the perception of mistreatment did not vary between both periods (before vs. during the pandemic), that is, before the pandemic it may be that the health personnel were already accustomed to these stimuli (action), to the point of not generating a response to them (reaction), considering it as an intrinsic part of their work, so it would not only be necessary to strengthen intervention strategies in the social environment that surrounds them (community), but also to evaluate the relevance of implementing strategic programs that directly address the health professional, seeking to strengthen and optimizetheir physical and mental health.